Unifying the applications and foundations of biomedical and health informatics - Mantas, J. (John); Hasman, Arie; Gallos, Parisis; Kolokathi, Aikaterini; Househ, Mowafa,d1977-eeditor (Studies in health technology and informatics ;vv. 226, 2016)
This book presents the proceedings of the 14th annual International Conference on Informatics, Management and Technology in Healthcare (ICIMTH), held in Athens, Greece, in July 2016. The conference treats the field of biomedical informatics in a very broad framework, and the 68 full papers included here examine the research and applications outcomes of informatics from cell to population, including a number of technologies such as imaging, sensors, mobile communications, biomedical equipment and management, as well as legal and societal issues related to the application of health informatics. The book is divided into sections: Biomedical Technology; Clinical Informatics; E-learning and Education; Formalisation of Knowledge, Ontologies, Clinical Guidelines and Standards of Healthcare; Health Informatics; Healthcare Management and Public Health; mHealth and Telemedicine; and Social Media and Health. Also included are two keynote speeches. Covering a wide spectrum of applications, the book will be of interest to all those working in the design, management and delivery of healthcare services whose work involves the development or use of biomedical informatics.